Illocutionary indicators of sarcasm in the genre of sports analytical articles - Ksenia A. Pavlova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The article focuses on the pragma-stylistic mechanisms of sarcasm in the genre of sports analytical articles. The genre, which represents a detailed analysis of a sporting event or phenomenon together with its evaluation, is an evaluative genre within the discursive space of sports. The pejorative evaluation manifests in various forms of verbal aggression, including sarcasm. Based on the theoretical research study, the correlation between sarcasm and irony is examined, and differentiating parameters that help distinguish two phenomena are identified. In the practical part a pragma-stylistic analysis of the most recurrent illocutionary indicators of sarcasm within the studies genre is provided.